Interference of Kailinese on Sentence Formation in Indonesian Among Indonesian High School Students - Ananta, Yasril; Putra, Rizky Anugrah (Yayasan Kyadiren, 2024)
This research investigates the impact of the Kaili Rai dialect on Bahasa Indonesia sentence construction among students at SMA Negeri 2 Sirenja, focusing on the forms and triggers of interference. Using a mixed-method approach, both qualitative and quantitative data were collected through sentences from stimuli, questionnaires, observation, interviews, and documentation. Data analysis involved the referential and orthographic equivalence methods. The study revealed 29 instances of intralingual interference and 65 of interlingual interference, totaling 94 specific errors: 50 omissions, 3 additions, 3 misinformation errors, 9 substitutions, and 29 sentence construction errors. Additionally, the research identified triggers for these errors, highlighting the impact of the Kaili language and a moderate level of low student motivation, as determined by the questionnaire results.